2021
DOI: 10.1002/ejoc.202101170
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of D‐Isoglutamine: Rapid Access to Desmuramyl Analogues of Muramyl Dipeptide for the Activation of Intracellular NOD2 Receptor and Vaccine Adjuvant Applications

Abstract: Muramyl dipeptide (MDP) -the smallest immunomodulatory unit of bacterial peptidoglycan -has adjuvant activity and triggers the innate immune system against bacterial and viral infections. The inherited drawbacks of MDP, such as pyrogenicity and poor macrophage penetration, can be resolved by structural modifications, thereby improving its pharmacological profile and adjuvant activity. Herein, several desmuramyl analogues of MDP were designed by replacing the carbohydrate fragment (MurNAc) of the parent molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Several SAR studies of NOD2 agonists have been reported, including synthetic modifications at the saccharide and peptide parts of MDP [ 7 , 8 , 19 , 20 , 21 ]. Carbohydrate moiety (muramic acid) can be replaced by different substituents [ 6 ] and increase of lipophilicity can lead to improved immunostimulating activity [ 7 , 8 , 9 , 22 ]. Mifamurtide (liposomal muramyl tripeptide phosphatidyl ethanolamine) is a synthetically modified MDP and a clinically used therapeutic agent [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several SAR studies of NOD2 agonists have been reported, including synthetic modifications at the saccharide and peptide parts of MDP [ 7 , 8 , 19 , 20 , 21 ]. Carbohydrate moiety (muramic acid) can be replaced by different substituents [ 6 ] and increase of lipophilicity can lead to improved immunostimulating activity [ 7 , 8 , 9 , 22 ]. Mifamurtide (liposomal muramyl tripeptide phosphatidyl ethanolamine) is a synthetically modified MDP and a clinically used therapeutic agent [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mifamurtide, phospholipids facilitate the incorporation of the peptide part into liposomes due to the lipophilicity. Therefore, the introduction of lipophilic substituents has been the mainstream of SAR studies [ 6 ]. Our research is focused on the preparation of MDP mimetics, primarily modified by lipophilic adamantane due to the fact that adamantane DMPs are devoid of the undesirable side-effect [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations